INFLUENCE OF TOP LEADERSHIP SUPPORT ON CUSTOMER RELATIONSHIP MANAGEMENT IN PRIVATE HOSPITALS IN KENYA - Muthigah, Faithmercy; Kiragu, David; Sang, Anne (Journal of Human Resource and Leadership, 2021)
Purpose: The purpose of this study was to evaluate the influence of top leadership support on customer relationship management in private hospitals in Kenya Materials and Methods: The study adopted descriptive survey design. It targeted 161 private hospitals which are accredited by NHIF in Kenya and which formed the unit of analysis of the study. Simple random sampling was then be used to obtain the 644 respondents. The researcher utilized a structured questionnaire with a five-point Likert scale to gather the data. The collected data was coded and entered in SPSS for further analysis. Descriptive and inferential analysis was conducted. Before inferential analysis was conducted, diagnostics tests were done. Results: The study confirmed that there existed a statistically significant relationship between top leadership support and customer relationship in Kenya, rejecting the null hypothesis and supporting the alternative hypothesis that there is a positive relationship between top leadership support and CRM. Top leadership explained 58.5% of CRM and this implies that if private hospitals boost top leadership support like staff motivation, delegation of duties, mentorship and coaching and strategic planning, staff morale would increase leading to high performance Unique contribution to theory, practice and policy: The study recommends that top leaders/management should support strategic policy process from formulation, development all through to implementation to ensure effective application of CRM in their institutions.